Filozofija predmeta, geometrija in fizika - konstruktivizem - Vrečko, Janez (Primerjalna književnost, 2010)
This article deals with the time and space issues of Srečko Kosovel's conses. It shows how Kosovel used them to accomplish a rare example of literary constructivism in Europe. Among other things, this is evident from a "geometric," engineering, physics, and Einsteinian analysis of Sferično zrcalo (Spherical Mirror). The pictorial effect of the letter K is actually an effect of the construction lines used by the poet to achieve the depth of space. The lyric subject is banished from the poem, but enters it as a constructor; in this, K for konstruktor "constructor" and K for Kosovel the poet happen to overlap in an ideal way.
Keywords: Kosovel, Srečko, 1904-1926; slovenska poezija; literarna avantgarda; constructivism; konstruktivizem